2011
DOI: 10.4028/www.scientific.net/amr.250-253.3012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Pavement Performance for Sandy Soil Stabilized by Soil Stabilizer

Abstract: In order to protect natural environment and save construction cost, both the physical and mechanical properties and the strength change laws of stabilized sandy soil mixture were studied in this paper based on the characteristic of sandy soil stabilized by Lufeng-1 soil stabilizer. The results show that the pavement performance indexes of the sandy soil stabilized by soil stabilizer completely meet the design requirements of every pavement structure layer below base in certain proportion and the optimum propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After modification by a stabilization agent, the silt soil exhibits an increased compactness and decreased water content, along with an improved physical property and mechanical performance [ 8 ]. Previous studies demonstrated that the stabilized soil can be used as a preferable construction material due to its good volume stability, mechanical properties, freeze-thaw resistance and low engineering cost [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…After modification by a stabilization agent, the silt soil exhibits an increased compactness and decreased water content, along with an improved physical property and mechanical performance [ 8 ]. Previous studies demonstrated that the stabilized soil can be used as a preferable construction material due to its good volume stability, mechanical properties, freeze-thaw resistance and low engineering cost [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%